The labour alienation of civil servants in Zimbabwe: Towards an ubuntu spirituality of work - Manobo, Blazio M. (HTS teologiese studies, 2024)
The alienation of labour is both classical and contemporary. In its classical form, it speaks to the potential dehumanisation of workers in capitalist societies. In its contemporary form, it manifests itself in the disenfranchisement of the individual because of changes in organised global workplaces. Over the years, Africa’s labour transition from traditional spirituality to contemporary organised global workplaces has fuelled new forms of public labour alienation. Civil servants, in some African countries, experience labour alienation reminiscent of work under capitalism. This is in contradiction to the pre-colonial and traditional view of work as a vocation. Zimbabwe is undergoing negative economic, social, and political growth that has resulted in the alienation of civil servants. The government reneges on its public role of providing space for individual growth and well-being in preference for ‘public capitalism’ and cultural alienation. The potential for an effective public service lies in changing the work culture.Contribution: This article interrogates the impacts of the work culture within the public service in Zimbabwe in an attempt to proffer a return to the African traditional spirituality of work that was founded on the principles of ubuntu. It recognises the traditional symbiotic relationship between being and doing among the indigenous African communities as the panacea for the continent’s human capital development.